An overview of some key researchers and topics in environment-behavior studies and some implications for architectural and environmental design - Habib, Jamshid (Kansas State University, 2010)
This thesis provides an overview of some key researchers and research topics in the field of environment-behavior studies (EBS), an interdisciplinary field that examines ways in which the natural and human-made environments contribute to human well-being. A key aim of environment-behavior studies is to better understand clients’ and users’ environmental needs, and to design the physical environment accordingly. Specifically, this thesis highlights two key research questions: (1) What are environment-behavior studies and why are they relevant to architecture and environmental design? and (2) How can environment-behavior studies be drawn upon practically to generate more effective architectural and environmental design? To provide answers to these two questions, the thesis first introduces five “pioneers” in environment-behavior studies— psychologist Roger Barker, anthropologist Edward Hall, psychologist Robert Sommer, urban designer Kevin Lynch, and architect Christopher Alexander—and reviews their major work. This discussion provides a general understanding as to what environment-behavior studies involve and how they have design significance. Next the thesis overviews three major theories developed in environment-behavior studies: (1) territoriality theory; (2) cognitive-mapping theory; and (3) prospect-refuge theory. Each of these theories is overviewed, and pragmatic examples are provided to indicate each theory’s value for architecture and environmental design.
Keywords: Environment & behavior studies; Architecture; Design; Territoriality; Cognitive mapping; Prospect-refuge theory; Architecture (0729); Geography (0366); Urban and Regional Planning (0999)